Individual Responses to Affirmative Action Issues in Criminal Justice Agencies, 1981: (United States) - Feyerherm, William H. ([Verlag nicht ermittelbar], 1990)
These data, which are part of a larger study undertaken by the University of Wisconsin-Milwaukee, evaluate the responses of criminal justice employees to affirmative action within criminal justice agencies. Information is provided on employees' (1) general mood, (2) attitudes across various attributes, such as race, sex, rank, education and length of service, and (3) demographic characteristics including age, sex, race, educational level, parents' occupations, and living arrangements. The use of criminal justice employees as the units of analysis provides attitudinal and perceptual data in assessing affirmative action programs within each agency. Variables include reasons for becoming a criminal justice employee, attitudes toward affirmative action status in general, and attitudes about affirmative action in criminal justice settings.